2015
DOI: 10.3310/phr03030
|View full text |Cite
|
Sign up to set email alerts
|

Can community-based peer support promote health literacy and reduce inequalities? A realist review

Abstract: BackgroundCommunity-based peer support (CBPS) has been proposed as a potentially promising approach to improve health literacy (HL) and reduce health inequalities. Peer support, however, is described as a public health intervention in search of a theory, and as yet there are no systematic reviews exploring why or how peer support works to improve HL.ObjectiveTo undertake a participatory realist synthesis to develop a better understanding of the potential for CBPS to promote better HL and reduce health inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 139 publications
5
84
0
2
Order By: Relevance
“…In addition, studies from the US and the UK have shown that limited health literacy in the elderly population is independently associated with increased mortality . Lower health literacy is a public health issue which has been shown to follow a social gradient, potentially reinforcing existing health inequalities …”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies from the US and the UK have shown that limited health literacy in the elderly population is independently associated with increased mortality . Lower health literacy is a public health issue which has been shown to follow a social gradient, potentially reinforcing existing health inequalities …”
Section: Introductionmentioning
confidence: 99%
“…Self‐management programmes for people with arthritis have been delivered effectively in community settings (Lorig et al, ), and research suggests that programmes using lay tutors can improve health outcomes (Best et al, ; Kennedy et al, ). Social and community networks are vital in supporting self‐management behaviour in long‐term conditions (Blickem et al, ), and personal and societal factors play an important role in supporting individuals to engage with self‐management approaches (Boger et al, ; Greenhalgh, ; Harris et al, ). This suggests that community [non‐National Health Service (NHS)] settings could provide supplementary environments for delivering information and skills relating to managing long‐term conditions, such as OA.…”
Section: Introductionmentioning
confidence: 99%
“…By looking across cases, patterns can be identified, the result of similar mechanisms being triggered in some contexts. Realist evidence synthesis develops descriptions of these patterns from which realist researchers seek to develop “middle‐range” theories which are “close enough to the data that testable hypotheses can be derived from it, but abstracted enough to apply to other situations as well.” A recent realist review considered community‐based peer support across a range of health topics (Harris et al, ); however, this did not encompass the models of one‐to‐one BFPS that had been subject to experimental study and whose findings have been critiqued (Thomson & Trickey, ).…”
Section: Realist Review Of Experimental Studies Of Breastfeeding Peermentioning
confidence: 99%